The Routledge History Handbook of Central and Eastern Europe in the Twentieth Century.
1 online resource (384 pages).
Keywords: Violence analyses both the violence exerted on the societies of Central and Eastern Europe during the twentieth century by belligerent powers and authoritarian and/or totalitarian regimes and armed conflicts between ethnic, social and national groups, as well as the interaction between these two phenomena. Throughout the twentieth century, Central and Eastern Europe was particularly hard hit by war, violence and repression, with armed conflicts in the Balkans at the start and end of the period and two world wars in between. In the shadow of these full-scale wars, ethnic, social and national conflicts were intensified, found new forms and were violently played out. The interwar period witnessed the emergence of authoritarian states who enforced their claim to power through continued violence against political opponents, stigmatized ethnic, national, and social groups, and were themselves fought with subversive or terrorist techniques. This volume focuses specifically on physical violence: war and civil war, ethnic cleansing, systematic starvation policies, deportations and expulsions, forced labour and prison camps, persecution by state security - such as intensive surveillance, which had enormous impact on the lives of those it affected - and other forms of government oppression and militant resistance. Geographically, it considers the western regions of Belarus and Ukraine as sites of extreme violence that had noticeable impact on neighbouring Central and Eastern European countries as well. The concluding volume in a four-volume set on Central and Eastern Europe in the twentieth century, it is the go-to resource for those interested in violence in this complex region.